Dexmedetomidine prevents cardiomyocytes from hypoxia/reoxygenation injury via modulating tetmethylcytosine dioxygenase 1-mediated DNA demethylation of Sirtuin1. Issue 4 (1st April 2022) - Wang, Li; Wang, Shaowei; Jia, Tong; Sun, Xiaojia; Xing, Zhen; Liu, Hui; Yao, Jie; Chen, Yanlin
ABSTRACT: Myocardial hypoxia/reoxygenation (H/R) injury is a common pathological change in patients with acute myocardial infarction undergoing reperfusion therapy. Dexmedetomidine (DEX) has been found to substantially improve ischemia-mediated cell damage. Here, we focus on probing the role and mechanism of DEX in ameliorating myocardial H/R injury. Oxygen–glucose deprivation and reoxygenation (OGD/R) were applied to construct the H/R injury model in human myocardial cell lines. After different concentrations of DEX's treatment, cell counting kit-8 (CCK-8) assay and BrdU assay were employed to test cell viability. The profiles of apoptosis-related proteins Bcl2, Bax, Bad and Caspase3, 8, 9 were determined by Western blot (WB). The expression of inflammatory factors interleukin 1β (IL-1β) and tumor necrosis factor-α (TNF-α) was checked by reverse transcription-polymerase chain reaction (RT-PCR). By conducting WB, we examined the expression of NF-κB, Sirt1, Tet methylcytosine dioxygenase 1 (TET1) and DNA methylation-related proteins (DNA methyltransferase 1, DNMT1; DNA methyltransferase 3 alpha, DNMT3A; and DNA methyltransferase 3 beta, DNMT3B). Our data showed that OGD/R stimulation distinctly hampered the viability and elevated apoptosis and inflammatory factor expression in cardiomyocytes. DEX treatment notably impeded myocardial apoptosis and inflammation and enhanced cardiomyocyte viability. OGD/R enhanced total DNA methylation levels in cardiomyocytes, while DEX curbed DNA methylation. In terms of mechanism, inhibiting TET1 or Sirtuin1 (Sirt1) curbed the DEX-mediated myocardial protection. TET1 strengthened demethylation of the Sirt1 promoter and up-regulated Sirt1. DEX up-regulates Sirt1 by accelerating TET1 and mediating demethylation of the Sirt1 promoter and improves H/R-mediated myocardial injury. ABSTRACT: uf0001